PREPARING THE TEACHER FOR THE USE OF THEATRALIZED TEACHING MATERIALS IN PRIMARY SCHOOL - Blahun, Nataliia (Mountain School of Ukrainian Carpaty, 2021)
In the article investigated that modern educational classes of schoolchildren are based mostly on a rationally logical way of acquiring knowledge. If the emotional sphere of the personality is not involved, then the sensory abilities gradually atrophy. It is highlighted that in the modern sense, "free time" should be rationally organized to stimulate the formation of motivated creative initiative. It is determined that theatrical activity is a source of feelings development, experiences, and discoveries of the preschooler, which attracts him to spiritual values and is a concrete, visible result. It is analyzed that the real theatrical activity is a synthesis of physical, emotional, and intellectual activities of the participants of the action, built on its playful nature. It is proved that the game activity in the theatrical action is expressed in the physical, emotional, and intellectual game activity of the participants. Gradually increasing the activity of the games used leads to increased activity of participants, reaching its peak in the climax. The works of well-known modern teachers are considered, which allows us to conclude that the technological approach in the design of pedagogical processes is becoming qualitatively new for modern pedagogy. The basis of theatrical technologies is their interactive nature and artistic and pedagogical orientation. The process of creating a pedagogical action is modeled. It is proved that if the presence of the spectator is not expected, i.e. the action is built in the form of a scripted game, all children are involved in the game, i.e. the creative activity of the participants is limited by the script, the unpredictability is lost. If the spectator takes part in a theatrical action, then he gets the share of activity that is inherent in the spectator of a theatrical performance, that is, he only contemplates, empathizes, and feels involved in activities on stage. In this version, the spectator is not a full participant in the action but acts more as an object of influence of performers and actors. Audience activity is not programmed in such a play.